2014
DOI: 10.4081/ejh.2014.2415
|View full text |Cite
|
Sign up to set email alerts
|

Investigating conversion of endplate chondrocytes induced by intermittent cyclic mechanical unconfined compression in three-dimensional cultures

Abstract: Mechanical stimulation is known to regulate the calcification of endplate chondrocytes. The Ank protein has a strong influence on anti-calcification by transports intracellular inorganic pyrophosphate (PPi) to the extracellular matrix. It is known that TGF-β1 is able to induce Ank gene expression and protect chondrocyte calcification. Intermittent cyclic mechanical tension (ICMT) could induce calcification of endplate chondrocytes by decrease the expression of Ank gene. In this study, we investigated the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Recent evidence demonstrated that appropriate tension stimulation can maintain the secretory function of endplate chondrocytes, while excessive tension stimulation can inhibit the synthesis of ECM by endplate chondrocytes. However, short‐term tension stimulation does not weaken the viability of endplate chondrocytes, suggesting that tension stimulation does not directly bring about the death of endplate chondrocytes when first loaded, but instead leads to endplate chondrocyte degeneration through other signaling pathways . Therefore, clarification of the molecular mechanism underlying tension‐induced endplate chondrocyte degeneration and enhancement of stress resistance may be crucial to delay or reverse early degeneration of endplate cartilage …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrated that appropriate tension stimulation can maintain the secretory function of endplate chondrocytes, while excessive tension stimulation can inhibit the synthesis of ECM by endplate chondrocytes. However, short‐term tension stimulation does not weaken the viability of endplate chondrocytes, suggesting that tension stimulation does not directly bring about the death of endplate chondrocytes when first loaded, but instead leads to endplate chondrocyte degeneration through other signaling pathways . Therefore, clarification of the molecular mechanism underlying tension‐induced endplate chondrocyte degeneration and enhancement of stress resistance may be crucial to delay or reverse early degeneration of endplate cartilage …”
Section: Discussionmentioning
confidence: 99%
“…Regarding cellular vitality, short-term moderate tension stimulation helps maintain the stable phenotype and characteristics of endplate cells. In contrast, prolonged tension stimulation can induce degeneration and calcification of endplate cartilage, while it does not impact the viability of endplate chondrocytes during the early stage of stimulation [ 23 ]. Instead, it triggers degenerative changes through other signalling pathways.…”
Section: Mechanical Microenvironment Of the Cepmentioning
confidence: 99%
“…The effect of experimental treatments or disease on the fibrous joint tissue 43,44 and cartilage 45,46 were also investigated in papers falling into the category Experimental Medicine & Animal Models. 43-54 In this article group, conventional histochemical techniques, histological examination and morphometry at light and electron microscopy were often used together with immunohistochemistry, to describe the structural organization of brain 46 or the skeletal muscle 47 in mice strains, and to investigate in rats the effects of a maternal dietary load of alpha-tocopherol on the synapse density and glial synaptic coverage in the hippocampus of adult offspring.…”
Section: Tumor Biology and Markers Non-tumors Diseases Experimental Mmentioning
confidence: 99%
“…43-54 In this article group, conventional histochemical techniques, histological examination and morphometry at light and electron microscopy were often used together with immunohistochemistry, to describe the structural organization of brain 46 or the skeletal muscle 47 in mice strains, and to investigate in rats the effects of a maternal dietary load of alpha-tocopherol on the synapse density and glial synaptic coverage in the hippocampus of adult offspring. 48 Enzyme histochemistry and immunolabeling were simultaneously applied to describe the structural and functional organization of fatty livers submitted to a preservation procedure especially suitable for organ transplantation.…”
Section: Tumor Biology and Markers Non-tumors Diseases Experimental Mmentioning
confidence: 99%